STRENGTHENING THE CHARACTER OF READING THROUGH THE USE OF READING CORNER IN ELEMENTARY SCHOOLS - Ratnaningsih; Wakhudin Wakhudin; Subuh Anggoro; Ine Kusuma Aryani (SOSIOEDUKASI, 2026)
Character education in elementary schools is important but requires effective strategies to foster sustainable reading habits. This study aims to analyze the strengthening of reading habits through reading corners in elementary schools. This type of research is qualitative with a case study method. The study was conducted at SDN Patimuan 01 Cilacap with subjects of 4 teachers, 6 students in grades IV–VI, and 1 principal. Data were collected using observation, interviews, and documentary studies. Data were analyzed interactively with the stages of data condensation, data presentation, and drawing conclusions. Data were checked for validity through triangulation of sources and techniques. The results of the study indicate that the strengthening of reading habits in elementary school students developed significantly through the use of planned and contextual reading corners. Five main characters were formed, including (1) discipline through the habit of reading regularly according to schedule and consistent teacher guidance; (2) curiosity by exploring reading content; (3) critical reasoning through in-depth understanding, reflection, and creative projects; (4) independence emerged when having the initiative to choose their own books, write reviews, and recommend reading to friends; and (5) responsibility through positive attitudes towards reading, such as returning books on time, keeping the reading corner clean, and respecting friends' books. This emphasizes that the reading corner is not just a literacy facility but a strategic tool in forming a character that loves reading in a sustainable manner. Support from schools, parents, and the social environment is important for building a sustainable literacy ecosystem so that students' reading habits and literacy behavior develop consistently at school and at home.